Choosing whether to compete: Price and format competition with consumer confusion - Alexia Gaudeul; Paolo Crosetto (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We present results from a market experiment where firms with identical products can choose not only their price but also the format of their product. Products with different formats are difficult to compare but products with the same format are directly comparable. Savvy consumers buy the lowest priced of those products with the same format. We find that firms are unlikely to adopt the same format if there are many savvy consumers and firms can observe each other's decisions. Increases in the number of savvy consumers then lead to higher average prices. We argue that tacit collusion is at the origin of this result. Patterns in the evolution of prices give further support to this hypothesis.
Keywords: L15; D18; D43; 330